Analysis of Twitter-based Malware Propagation using SIR Epidemic Model - Yonathan, Alfius (Swiss German University, 2018)
This paper presented an analysis of malware propagation scenario in which attacker exploit news spreading dynamics on Twitter. The malware propagation starts with an attacker crafting tweets about breaking news, event or tragedy that will lure user to click the short-URL provided in the tweet which then redirect user to malicious website, which in turn installed the malware in the user mobile device or computer. As the information spread in the Twitter then more users will be infected with malware. The underlying principle to analyze this type of malware propagation is that the spreading of information in Twitter can be modeled by using formal epidemic model of disease. The simulation result of the model shows parameters that highly impacting the spread of malware using Twitter as the medium.